Modification of mechanical and color properties of polypropylene with colored nano‐SiO2 prepared from diatomite. Issue 5 (2nd August 2019) - Ma, Qianer; Xia, Meisheng
ABSTRACT: Diatomite powder was dissolved in alkali to form sodium silicate, which was then used to prepare colored nano‐SiO2 (CNS) by the process of chemical precipitation. The CNS was analyzed by means of X‐ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, and transmission electron microscopy. To explore the application of colored nano‐SiO2 in polypropylene (PP), CNS was incorporated into PP T30s. The mechanical and colorimetric properties of prepared CNS/PP composites were also investigated. The results of tensile tests indicated that the nanoparticles could simultaneously provide PP with stiffening, strengthening, and toughening effects at a low filler content (typically 2% by volume). At the same time, with CNS filler, the PP composites acquired a bright red color. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48328. Abstract : The Graph of Polypropylene Filled with Different Concentrations of Colorful Nano‐silica.